Complex funeral practices : archaeo-anthropological reassessment of iberomaurusians and capsians contexts (paleolithic and epipaleolithic, Northwest Africa) - (:unkn) unknown (My University, 2013)
The iberomaurusien (23,000 - 9500 cal BC) and the Capsian (9600-5000 cal BC) are two cultures dating from the end of the upper Palaeolithic and Epipalaeolithic in North Africa. They have been established on the basis of the characterisitics of their lithic industries. The Iberomaurusien is characterized by a lamellar microblade industry and Capsian by a microblade industry rich in tiny segments and microburins microbladelets. Biological discontinuity of these two groups has been assumed on the basis of questionable anthropological arguments which have strongly influenced debate on their origins. Thus a Middle-Eastern origin has been proposed for the Capsian. We wanted to test this theory using a study of the mortuary practices in these two groups. By applying the perspective of modern mortuary anthropology, we offer a critical review of the entire available corpus. This includes 60 Iberomaurian graves, containing 126 individuals discovered in 10 sites, 48 Capsian graves containing 55 individuals from 13 sites, and 38 burials from the Columnata site providing 89 individuals. We carefully analyzed the contexts of discovery of these individuals as described in publications and field notes. We have revised the counts, the sex-determination and estimation of the age at death. We also explored the surface of the bones looking for stigmata to validate what a taphonomic analysis of the graves might reveal. We first characterized the burial system of each of these two groups, and then the components of these two systems were compared to find a possible transmission or break in burial custom between the two societies. The funeral practices as we have established them, confirm the specificity of these two groups. Funeral rituals are different and the absence of direct transfer between these two groups of hunter-gatherers is first considered. However, the osteo-archaeological interpretation of the graves revealed the presence of a (conditional) minority funeral cu
Keywords: African Research